masa66
contestada

The graph of a function g
is shown below.
Use the graph of the function to find its average rate of change from x=-3 to x=1
Simplify your answer as much as possible.

The graph of a function g is shown below Use the graph of the function to find its average rate of change from x3 to x1 Simplify your answer as much as possible class=

Respuesta :

*This is a maths problem.

Answer:

-2

Explanation:

Average rate of change of the function from x = -3 to x = 1 can be calculated using the formula below:

[tex] \frac{f(b) - f(a)}{b - a} [/tex]

Where,

[tex] a = -3, f(a) = 1 [/tex] (from the graph, when x = -3, y = 1)

[tex] b = 1, f(b) = -7 [/tex] (from the graph, when x = 1, y = -7)

Plug in the values into the formula:

[tex] = \frac{-7 - 1}{1 -(-3)} [/tex]

[tex] = \frac{-8}{4} [/tex]

[tex] = -2 [/tex]

Average rate of change from x = -3 to x = 1 is -2.

ACCESS MORE